Rural tourism, hospitality and cultural tourism experiences: rural tourism business: case studies in Baixo Alentejo (Portugal) - Amaral, Marta Isabel (2020)
Rural tourism meets the needs of a growing group of urban consumers who seek to break away from everyday life and gain a reinvigorating, rural and authentic experience that integrates traditions, customs and local identity. Through its peculiar characteristics such as hospitality and its symbolic materials, rural tourism company owners have an opportunity to diversify their activities here. The offer of interactive and dynamic experiences refers to the singularity of places and the personalization of experiences, which are decisive factors in the affirmation of destinations with rural characteristics and for the differentiation of rural tourism establishments. The present research presents the first phases of an investigation using a set of semistructured interviews with the owners of rural settlements (rural tourism), with selection based on their location in the county, their size and the experiential activities they promote and that are disseminated through communication channels. The aspects considered in the collection of data are related to the need to deduce the symbols of hospitality, characterized by history, local culture, gastronomy and tradition, along with other aspects that influence good service. From the analysis of the results, it was possible to conclude that rural tourism establishments, know well what tourists are looking for in rural space and develop several activities (individual or in partnership) to attend their needs. The managers also reveal distinguished behaviour to give a personalized and high-quality customer service.